ANALISIS TERHADAP PENOLAKAN RAPERDA ZAKAT BAGI MASYARAKAT MUSLIM KOTA METRO - Nurjanah, Siti (P3M STAIN Jurai Siwo Metro, 2011)
The rule of zakat in Indonesia is found in law Number 38 year 1999 on the management of zakat. But, there isnt binding rules of procedure which resulted in its management feesÂ that cant run optimally. Even though there is institution which manage zakat wealth, BAZIS, but if it also wasÂ able to do a good role without binding rule? Metro City where its most population are muslim doesnt have solid fundation for optimizing the potencial of zakat. So the Council of Indonesian Ulama (MUI) of Metro City proposes to parlement and executive to make zakat legal drafting. Majority of parlement member rejected those legal drafting. This research aims to axplore the real reason of parlement member to reject zakat legal drafting. The research is field research in which the data obtained by interview. The result shows that the real reason of rejection parlement member of Metro City is political interest. The legal drafting of zakat legislation has been discussed in parlement before the legislative election in Indonesia. Some might be worried if certain party votes because of its proposing the regional regulation of zakat.Â Key Word : Penolakan, Raperda Zakat, kepentingan politik, Urusan Agama